Experiences and Challenges Perceived by Indonesian EFL Teachers as Non-Native English Speaker Teachers (NNESTs) in Thailand - Vincentia Aprilla Putri (Universitas Islam Negeri Walisongo Semarang, 2020)
This study investigated the experiences and challenges perceived by Indonesian EFL teachers as the NNESTs in Thailand. The study used a questionnaire and interviews to collect primary data from seventeen Indonesian EFL teachers in Thailand. The study discovered that most of the Indonesian EFL teachers are eager to teach English in Thailand to have teaching experience abroad, to improve their English skills, and to earn higher salaries. Besides, the Indonesian EFL teachers did not find difficulties in adapting to the new cultures in Thailand, even though adjusting to the teaching environment became a challenge. Moreover, third, the Indonesian EFL teachers were treated equally as the NESTs, although their salaries were lower than those of NESTs. Lastly, the study reported issues in English classes, such as students' motivations, linguistic gaps, and plagiarisms, which trigger the creativity of Indonesian EFL teachers in English classes.